Food Cravings and Eating: The Role of Experiential Avoidance - Fahrenkamp, Amy J. (Int J Environ Res Public Health, 2019)
Food cravings have been associated with problematic eating behaviors, such as emotional eating. Late adolescence is an important developmental period to examine this association, as late adolescents have greater independence in food choices as well as potentially higher demands during a transitional period of their lives. Mechanisms underlying the association between food cravings and problematic eating remain unclear. This study examined whether experiential avoidance (EA) may be one possible mechanism mediating the association between higher levels of food cravings and problematic eating behaviors. Late adolescents (n = 174) completed measures assessing EA, food cravings, and three problematic eating behaviors: emotional eating, cognitive restraint, and uncontrolled eating. Height and weight were measured objectively to calculate body mass index (BMI). Food cravings were positively associated with emotional eating and mediated by EA. EA also significantly mediated the association between greater cognitive restraint and greater food cravings. No significant mediation was detected for food cravings and uncontrolled eating. Future research may consider EA as a treatment target in intervention strategies for late adolescents seeking to decrease emotional or restrained eating behaviors.